Women Prisoners: Freedom From Sexual Harassment - A Constitutional Analysis - Hanson, Laurie A. (2010)
Sexual harassment of female inmates by male guards permeates American prisons because the imbalance of power between the guard and the prisoner allows and encourages it to exist. Sexual harassment in prison is not a series of isolated incidents; rather, it is so much a part of the power structure that it is almost invisible. There are few reported cases of sexual harassment of women prisoners. Until recently sexual harassment, even outside the prison, went unnoticed. Also, if a prisoner reports sexual abuse, the prison administration will generally blame the prisoner, or deny the accusation, but only occasionally fire the guard. Consequently, prisoners infrequently report abuses. Further, women prisoners as a class have received little attention. They do not bring lawsuits to protest grievances because they fear for their own safety. It is difficult for women prisoners to gain access to the courts due to a lack of available services within the prisons. In recent years, however, interest in female prisoners' plight has been renewed. Suits have been filed on their behalf which have identified issues unique to them, including rape and sexual abuse by guards and the right to bodily privacy